Trends and geographic patterns of overweight and obesity among Tanzanian adults: Evidence from the 2010–2022 Demographic and Health Surveys - Angelina Mageni Lutambi; Gerald Phares Mwing’a; Basiliana Emidi (PLoS ONE, 2025)
Overweight and obesity are risk factors for several non-communicable diseases. In Tanzania, despite the increasing public health concern, detailed spatial information on the distribution of overweight and obesity is limited. This study aimed to determine the prevalence, show spatial and temporal variations and identify factors that impact overweight and obesity in Tanzania. We used cross-sectional survey secondary data from the Tanzanian Demographic and Health Surveys (DHS) which collected anthropometric measurements in women aged 15−49 years in 2010, and 2015−16, and both women and men in the 2022 survey. Spatial interpolation was performed to estimate prevalence at unsampled locations, while generalized additive models were used to identify factors and assess their effect on the spatial distribution of overweight and obesity risk. The study included 33,787 participants (9,029 in 2010, 11,940 in 2015−16, and 12,818 in 2022). The overall mean age was 29 (SD = 10) years. The prevalence of overweight and obesity among women increased by 45.45%, rising from 22% in 2010 to 32% in 2022, with higher rates observed in urban areas and among wealthier and more educated women. In 2022, women were disproportionately affected, with 32% being overweight or obese compared to 15% of men, and 45% were urban women and 23% urban men. Age and wealth index were consistent significant factors across all surveys while place of residence was a significant factor in 2010 and 2015. Geographic disparities were evident, with the eastern, southern highlands, and northern regions showing higher prevalence compared to the lake zone. Overweight and obesity are increasing in Tanzania, driven by wealth and age. Urban residence was a significant factor in early years and its influence declined in 2022. The observed regional disparities highlight the urgent need for targeted and multi-sectoral interventions.